Detection of The Deaf Signal Language Using The Single Shot Detection (SSD) Method - Dadang Mulyana Iskandar; Mesra Betty Yel; Aldi Sitohang (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
Sign Language is a language that prioritizes manual communication, body language, and lip movements, instead of sound, to communicate. Deaf people are the main group who use this language, usually by combining hand shape, orientation and movement of the hands, arms, and body, and facial expressions to express their thoughts. Therefore, the researcher created an image recognition program in sign language using the Single Shot Detection (SSD) method, which is a convolution activity by combining several layers of preparation, by utilizing several components that move together and are motivated by a biological sensory system. The letters used in making sign language programs use the letters of the alphabet (az). This sign language detection programming that runs on the Google Collaboratory application